Vacuum Electronics Components and Devices - Eichmeier, Joseph A.; Eichmeier, Joseph A.; Thumm, Manfred.; Thumm, Manfred. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
Nineteen experts from the electronics industry, research institutes and universities have joined forces to prepare this book. Vacuum Electronics covers the electrophysical fundamentals, the present state of the art and applications, as well as the future prospects of microwave tubes and systems, optoelectronics vacuum devices, electron and ion beam devices, light and X-ray emitters,particle accelerators and vacuum interrupters. These topics are supplemented by useful information about the materials and technologies of vacuum electronics and vacuum technology.